Through A Strangers' Eyes: From Stranger to Familiar A Phenomenological Journey Exploring High School Students' Understanding of Culture Through Participation in the Human Geography Class - Dyer, Steffani Parker (My University, 2018)
A sound understanding of culture is an important concept for students to acquire in a globalized world. Despite researchers’ interest in how individuals understand culture, little research has focused on high school students’ understanding of culture. In fact, most research exploring high school students understanding of culture has examined the concept using quantitative methods to determine their level of understanding of other cultures. To that end, no study that I have found thus far, has examined the process of the shifting conceptualization that high school students experience from participating in a human geography course. Thus, this study sought to shed light on emic narrative voices of the 10 high school students’ journey with shifting conceptualization of culture from participating in a human geography course. The purpose of this study was to explore students’ understanding of culture from taking the human geography class. More specifically, the particular interest of this study was to examine the processes and outcomes of shifting conceptualization of culture that 10 high school students experienced from participating in a human geography class. Using a post-intentional phenomenological framework, I followed and applied Vagle’s (2014) five-component process to examine the phenomenon. Qualitative data were collected through expressive writings, focus group interviews, and semi-structured interviews in an attempt to capture students’ voices of their experiences in the human geography class that led to their shifts in their conceptualization of culture. The data were then analyzed using the whole-part-whole process (Vagle, 2014), and examined for tentative manifestations of the phenomenon. Participants verbatim focus group and individual narratives are offered in the findings chapter. Data analysis revealed four distinct themes or tentative manifestations that were ubiquitous among all of the participants: shifts in conceptualization of culture that lead to deeper, more complex thought than previously experienced, changes in thinking patterns related to culture, shifts in conceptual thinking that led to changes in behavior that resulted in a greater level of tolerance and acceptance of others, and shifts in conceptualization of culture that resulted in that transfer of knowledge and real-life application of culture. These tentative manifestations are discussed in greater detail in the tentative manifestation chapter. The findings in the study indicated that students developed a greater understanding of culture that became more complex and broader than they initially thought while also experiencing a shift in their thinking patterns related to culture after participating in a human geography class. Further, shifts in their conceptualization of culture led to changes in their behavior that leading to a greater level of tolerance acceptance and open-mindedness about culture, and transfer of knowledge to real-life application of information that would ultimately benefit them in the future. Finally, a discussion of implications and limitations of the study and future research are offered.
Chapter I: INTRODUCTION 1 -- Background of the Study 1 -- Significance of the Study 6 -- Purpose of the Study 12 -- Research Questions 13 -- Conceptual Framework 14 -- Personal Interest 15 -- Professional Interest 17 -- Personal Position in the Study 19 -- Theoretical Framework 20 -- Summary 21 -- Chapter II: REVIEW OF THE LITERATURE 23 -- Trends in Immigration 23 -- Understanding the Concept of Culture 25 -- The Research 28 -- Quantitative Research 28 -- College Level 28 -- High School and Middle School Level 30 -- Qualitative Research 34 -- Mixed-Method Research 37 -- College Level 37 -- Middle School Level 41 -- Summary 42 -- Chapter III: METHODS 44 -- Phenomenology 44 -- Post-Intentional Phenomenology 49 -- Design of the Study 55 -- Research Component 1: Identify the Phenomenon 56 -- Contexts 57 -- Participant Selection 59 -- Participant Selection Procedure 60 -- Summary 63 -- Research Component 2: Devise a Clear, Yet Flexible Plan to Gather Data 64 -- Select Data Sources 64 -- Align Data Sources with Research Questions 69 -- Summary 69 -- Research Component 3: Make a Post-Reflexion Plan 70 -- Create A Post-Reflexion Journal 71 -- Write an Initial Post-Reflexive Statement 73 -- Post-Reflex as You Gather and Analyze Data 76 -- Summary 77 -- Research Component 4: Read and Write Your Way Through the Data in a Systematic, Responsive Manner 78 -- Whole-Parts-Whole 79 -- Step 1: Holistic Reading of the Entire Text 79 -- Step 2: First Line-by-Line Reading 80 -- Step 3: Follow-Up Questions 82 -- Step 4: Second Line-by-Line Reading 82 -- Step 5: Third Line-by-Line Reading 84 -- Step 6: Subsequent Readings 86 -- Summary 87 -- Research Component 5: Craft a Text that Captures Tentative Manifestations of the Phenomenon in its Multiple, Partial, and Varied Contexts 88 -- Re-State the Multiple and Varied Contexts. 88 -- Brainstorm Potential Forms. 89 -- Summary 90 -- Summary 90 -- Credibility 91 -- Summary 95 -- Chapter IV: INTERACTIVE FOCUS GROUP INTERVIEWS 96 -- Interactive Focus Group 1: NG 98 -- Topic 1: Reasons For Taking the Class 100 -- Topic 2: What is Culture 101 -- Topic 3: Vivid Experience 105 -- Topic 4: Culture as All-Encompassing Concept 110 -- Topic 5: New Look at Culture 112 -- Interactive Focus Group 1: EC 115 -- Topic 1: Reasons for Taking the Class 117 -- Topic 2: What is Culture 118 -- Topic 3: Pre-Class Awareness of Culture 120 -- Topic 4: Aha Moments 123 -- Topic 5: New Understandings 125 -- Topic 6: Vivid Memories 131 -- Summary of The First Focus Group Interviews 133 -- Individual Vignettes 133 -- Osceola 134 -- Athens 142 -- Kelly and Matthew 151 -- Georgia 162 -- Tess 170 -- Jefferson 178 -- Just Jim 190 -- Evangeline Harcourt 199 -- Shirley Shire 207 -- Summary 216 -- Interactive Focus Group 2: NG 217 -- Topic 1: Look at the World in New Ways 217 -- Topic 2: The Why of Where 220 -- Topic 3: Deeper Levels of Analysis 223 -- Topic 4: New, In-depth Understanding 226 -- Topic 5: Lightbulb Moments 228 -- Interactive Focus Group 2: EC 232 -- Topic 1: Look at the World in New Ways 232 -- Topic 2: The Why of Where 234 -- Topic 3: Deeper Levels of Analysis 237 -- Topic 4: New, In-depth Understanding 238 -- Topic 5: Lightbulb Moments 240 -- Summary of Final Focus Group Interviews 242 -- CHAPTER V: TENTATIVE MANIFESTATIONS 243 -- Tentative Manifestation 1: Shifts in Conceptualization of Culture to Deeper, More Complex Thought 243 -- Osceola 246 -- Athens 248 -- Kelly 250 -- Matthew 252 -- Georgia 253 -- Tess 255 -- Jefferson 257 -- Just Jim 258 -- Evangeline Harcourt 259 -- Shirley Shire 262 -- Summary of Tentative Manifesation 1 263 -- Tentative Manifestation 2: Shifts in Conceptualization of Culture that Led to Changes in Thought Patterns 265 -- Osceola 265 -- Athens 266 -- Kelly 267 -- Matthew 268 -- Georgia 270 -- Tess 271 -- Jefferson 272 -- Just Jim 273 -- Evangeline Harcourt 275 -- Shirley Shire 276 -- Summary Tentative Manifestation 2 279 -- Tentative Manifestation 3: Shifts in Conceptualization of Culture Led -- to Changes in Behavior Resutling in Greater Tolerance and Acceptance…... 280 -- Osceola 281 -- Athens 282 -- Kelly 283 -- Matthew 285 -- Georgia 286 -- Tess 287 -- Jefferson 288 -- Just Jim 290 -- Evangeline Harcourt 290 -- Shirley Shire 291 -- Summary Tentative Manifestation 3 292 -- Tentative Manifestation 4: Shifts In Concepetualization of Culture that Led to Transfer of Knowledge and Real-Life Application of the Concept of Culture.293 -- Osceola 294 -- Athens 295 -- Kelly 297 -- Matthew 298 -- Georgia 300 -- Tess 301 -- Jefferson 303 -- Just Jim 305 -- Evangeline Harcourt 307 -- Shirley Shire 308 -- Summary of Tentative Manifestation 4 310 -- Summary of All Tentative Manifestations 310 -- Conclusion 311 -- CHAPTER VI: DISCUSSION 313 -- Interpretation of the Findings Aligned to Research Questions 315 -- Research Question 1 Findings Answered by TM 1: Shifts Conceptualization of Culture that lead to Deeper, More Complex Thought 315 -- Summary 319 -- Research Question 2 Findings Answered by TM 2: Shifts in Conceptualization of Culture that Led to Changes in Thought Patterns 320 -- Summary 326 -- Research Question 3 Findings Answered by TM 3: Shifts in Conceptualization of Culture that Let to Changes in Behavior Resulting in Greater Tolerance and Acceptance 327 -- Summary 330 -- Research Question 3 Findings Answered by TM 4: Shifts in Conceptualization of Culture that Led to Transfer of Knowledge and RE 331 -- Summary 336 -- Limitations of the Study 337 -- Summary 339 -- Findings Related to The Literature 340 -- Summary 341 -- Implications 342 -- Summary 343 -- Future Research 344 -- Summary 345 -- Conclusion 345 -- EPILOGUE…. 347 -- REFERENCES 350 -- APPENDIX A: IRB APPROVAL 356 -- APPENDIX B: RECRUITMENT FLYER 359 -- APPENDIX C: INTEREST SURVEY 362 -- APPENDIX D: WRITING PROMPTS FOR LIVED EXPERIENCE DESCRIPTONS (LED) 364 -- APPENDIX E: SEMI-STRUCTURED INTERVIEW GUIDE 366 -- LIST of FIGURES -- Figure 1. Intentionality and Tentative Manifestations 51 -- Figure 2. Whole-Part-Whole Data Analysis Map 81 -- Figure 3. Sample of First Line-By-Line Procedure 83 -- Figure 4. Third Line-By-Line Reading Focus Group 2: Potential Tentative Manifestation 85
Keywords: Academic theses; Phenomenology; Focus groups; Interviewing; Vignettes; High school students; Cultural pluralism--Study and teaching (Secondary); Toleration--Study and teaching